Mycorrhizal status helps explain invasion success of alien plant species. Issue 1 (9th December 2016) - Menzel, Andreas; Hempel, Stefan; Klotz, Stefan; Moora, Mari; Pyšek, Petr; Rillig, Matthias C.; Zobel, Martin; Kühn, Ingolf
Abstract: It is still debated whether alien plants benefit from being mycorrhizal, or if engaging in the symbiosis constrains their establishment and spread in new regions. We analyzed the association between mycorrhizal status of alien plant species in Germany and their invasion success. We compared whether the representation of species with different mycorrhizal status (obligate, facultative, or non‐mycorrhizal) differed at several stages of the invasion process. We used generalized linear models to explain the occupied geographical range of alien plants, incorporating interactions of mycorrhizal status with plant traits related to morphology, reproduction, and life‐history. Non‐naturalized aliens did not differ from naturalized aliens in the relative frequency of different mycorrhizal status categories. Mycorrhizal status significantly explained the occupied range of alien plants; with facultative mycorrhizal species inhabiting a larger range than non‐mycorrhizal aliens and obligate mycorrhizal plant species taking an intermediate position. Aliens with storage organs, shoot metamorphoses, or specialized structures promoting vegetative dispersal occupied a larger range when being facultative mycorrhizal. We conclude that being mycorrhizal is important for the persistence of aliens in Germany and constitutes an advantage compared to being non‐mycorrhizal. Being facultative mycorrhizal seems to be especially advantageous for successful spread, as the flexibility of this mycorrhizal status may enable plants to use a broader set of ecological strategies.